Ultrasound-assisted investigation of photon triggered vaporization of poly(vinylalcohol) phase-change nanodroplets: A preliminary concept study with dosimetry perspective. (September 2021) - Toumia, Yosra; Miceli, Roberto; Domenici, Fabio; Heymans, Sophie V.; Carlier, Bram; Cociorb, Madalina; Oddo, Letizia; Rossi, Piero; D'Angellilo, Rolando Maria; Sterpin, Edmond; D'Agostino, Emiliano; Van Den Abeele, Koen; et al.
Highlights: Echography to assess photon-induced vaporization of perfluorobutane nanodroplets. Tuning the degree of superheat of nanodroplets enhances photon–triggered activation. New potential of phase change ultrasound contrast agents for radiotherapy dosimetry. Abstract: Purpose: We investigate the vaporization of phase-change ultrasound contrast agents using photon radiation for dosimetry perspectives in radiotherapy. Methods: We studied superheated perfluorobutane nanodroplets with a crosslinked poly(vinylalcohol) shell. The nanodroplets' physico-chemical properties, and their acoustic transition have been assessed firstly. Then, poly(vinylalcohol)-perfluorobutane nanodroplets were dispersed in poly(acrylamide) hydrogel phantoms and exposed to a photon beam. We addressed the effect of several parameters influencing the nanodroplets radiation sensitivity (energy/delivered dose/dose rate/temperature). The nanodroplets-vaporization post-photon exposure was evaluated using ultrasound imaging at a low mechanical index. Results: Poly(vinylalcohol)-perfluorobutane nanodroplets show a good colloidal stability over four weeks and remain highly stable at temperatures up to 78 °C. Nanodroplets acoustically-triggered phase transition leads to microbubbles with diameters <10 μm and an activation threshold of mechanical index = 0.4, at 7.5 MHz. A small number of vaporization events occur post-photon exposure (6MV/15MV), at doses between 2 and 10 Gy, leading to ultrasound contrast increase up to 60% at RT. The nanodroplets become efficiently sensitive to photons when heated to a temperature of 65 °C (while remaining below the superheat limit temperature) during irradiation. Conclusions: Nanodroplets' core is linked to the degree of superheat in the metastable state and plays a critical role in determining nanodroplet' stability and sensitivity to ionizing radiation, requiring higher or lower linear energy transfer vaporization thresholds. While poly(vinylalcohol)-perfluorobutane nanodroplets could be slightly activated by photons at ambient conditions, a good balance between the degree of superheat and stability will aim at optimizing the design of nanodroplets to reach high sensitivity to photons at physiological conditions.